Promoting global monetary and financial stability the Bank for International Settlements after Bretton Woods, 1973-2020 - Borio, Claudio E. V. ca. 20./21. Jh; Claessens, Stijn 1959-; Clement, Piet ca. 20./21. Jh; McCauley, Robert N. 1953-; Shin, Hyun Song 1959- (Cambridge University Press, 2020)
"When the BIS was established in 1930 it had two purposes. The most obvious practical concern was to handle a narrowly technical issue: to create a painless or crisis-minimising method for making the transfer of German postwar reparations payments. But the new institution also had a more encompassing goal, defined in its statutes, of promoting 'cooperation of central banks' in order to foster monetary stability."
Keywords: Bank für Internationalen Zahlungsausgleich; Geschichte; Bankenkrise; Finanzkrise; Finanzwirtschaft; Geldwirtschaft; Bank für Internationalen Zahlungsausgleich / (DE-588)1003374-9 / (DE-627)103013741 / (DE-576)191151114; 1973-2020; Internationale Wirtschaftsorganisation / (DE-627)091368480 / (DE-2867)10618-0; Internationales Währungssystem / (DE-627)091368731 / (DE-2867)10746-5; Internationales Finanzsystem / (DE-627)664032850 / (DE-2867)29222-2; Bankgeschichte / (DE-627)091349524 / (DE-2867)13691-3; Bank for International Settlements; Monetary policy; Aufsatzsammlung